For Love of Country: Apocalyptic Survivance in Ambelin Kwaymullina's Tribe Series. Issue 1 (2016) - Murphy, Graham J.
Abstract : Ambelin Kwaymullina, an Aboriginal writer, illustrator, and assistant professor who comes from the Palyku people of the Pilbara region of Western Australia, has most recently ventured into the popular realm of YA Dystopias with her Tribe trilogy: The Interrogation of Ashala Wolf (2012), The Disappearance of Ember Crow (2013), and The Foretelling of Georgie Spider (2015). Although the Tribe series aligns with the ecological utopia and Bildungsroman, it is more importantly a "teaching story" whose strength resides in its use of the apocalypse and the centralizing of Country as collective tactics of survivance and cultural brokering relevant to the experiences of living in a (post)colonial world.